Adoption of online food delivery by micro food service businesses: a conceptual paper / Izhar Hafifi Zainal Abidin, Mohd Onn Rashdi Abd Patah and Mohd Aliff Abdul Majid - Zainal Abidin, Izhar Hafifi; Abd Patah, Mohd Onn Rashdi; Abdul Majid, Mohd Aliff (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
With the increasing prevalence of the internet and technological improvements, more people are turning to online shopping as a convenient and efficient means of purchasing products and services, including food. In light of this recent development, adopting and utilizing third-party online food delivery (TPOFD) services are regarded as a viable alternative for food service businesses to cater to the demands of their customers. This action might also be regarded as a manifestation of service innovation on their behalf. However, although the benefits are well documented, only a modest percentage of micro-scale food service businesses have jumped on the bandwagon. It is apparent that to enhance the adoption rate, the inherent barriers must be directly addressed. One suggested approach is to embark on an exploratory journey into the complex adoption landscape of TPOFD services within the micro food service sector. Such an endeavor aims to elucidate the intricate adoption process, including the tangible impacts of adoption, the formidable obstacles encountered, and the strategies employed to surmount them. The significance of this research lies in its potential to provide a nuanced and comprehensive understanding of TPOFD adoption within micro food service businesses, to be a reference for those who do not yet adopt, and ultimately assist in organically improving the adoption rate. Beyond that, this study offers practical insights for industry practitioners, policymakers, and stakeholders, fostering a more informed and strategic approach to navigating the evolving landscape of food service delivery in the digital age.